Investigating the Impact of TikTok and Instagram Applications on Individuals’ Cultural Values and Self-Identification in Algeria: the case of Algerian youngsters - DEKHIL, Anfal khadidja (l’Université de Mostaganem, 2022)
The current study investigates the effects of the content of TikTok and Instagram applications on the cultural values and self-identifications of Algerian individuals. In this insight, on the one hand, we referred to the crucial role of the socialization institutions such as families and schools in transmitting and preserving the original cultural values and self-identification among youths because we observed that social media applications had substituted the original social institutions (families, schools and mosques). On the other hand, we mentioned the recent social change and local habits decline because of social media with its different applications, particularly TikTok and Instagram, since they are widely used by teenagers, moreover, how they could influence them unconsciously. These notions were illustrated by several theories, particularly Users' Gratification Theory, Dramaturgical Theory and Identity Theory. We adopted a netnographic research method using an online questionnaire and observation as the primary research instruments due to the targeted population's presence in two different platforms: two social media applications (TikTok and Instagram). Also, we designed a survey for each application to find suitable answers to the research questions because they differ in their content and influence. To collect appropriate data, we addressed 123 Algerian teenagers to answer the questionnaire of TikTok application and 161 Algerian teenagers for the Instagram application questionnaire, males and females. We designed some common questions to compare the results of both surveys and combine them at the end of the whole process in order to obtain general findings. The final results indicated that TikTok and Instagram applications have invaded Algerian teenagers’ minds and disturbed the flow of the local and inherited cultural values. Thus, they have substituted the cultural values and influenced teenagers’ self-identifications as an unavoidable result because they have shifted from the stage of media followers to media producers, content creators and influencers, which is a principal factor that contributes to losing the indigenous cultural values, traditional standards and affects the self-identifications of teenagers. They are present in two different spheres; hence, they remain vulnerable to these technological devices.
Keywords: Algerian teenagers, cultural values, Instagram, self-identification, social media, TikTok